KEKERASAN VERBAL DI RUANG DIGITAL : STUDI KASUS INFLUENCER PUTRI DI AKUN TIKTOK @PUTRIIPADANG - Dhevany; Iqbal, Muhammad (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study aims to determine the background of verbal violence on the Tiktok account @Putriipadang and explain the forms of verbal violence in the comments column on the Tiktok account @Putriipadang and describe the emotional impact and social impact that arises from verbal violence on the Tiktok account @Putriipadang. This research was conducted on the Tiktok account @Putriipadang. The method used in this study is Netnography. The data collection technique used is by using archives, data elicitation and field notes. The results of this study reveal that verbal violence on the Tiktok account @Putriipadang reveals that Putriipadang's viral content went viral because of its different physical appearance. The forms of violence in the comments column are in the form of insults, sarcasm and labeling of Putriipadang's face. The verbal violence of the Tiktok account @Putriipadang has an emotional impact in the form of feeling watched and psychological trauma received by Putriipadang. And also has a social impact by closing the comments column on one of his posts. Keywords: Verbal Violence; Digital Space; TikTok